EU Enlargement: Expanding the Union and Its Potential - Jiffer Bourguignon; Maria Demertzis; Ekaterina Sprenger (Intereconomics)
Abstract The new EU member candidates, as well as those who have had this status for a decade, present the Union with an opportunity to decide what kind of club it should be.